Chemical contributions to silicon anode calendar aging are dominant over mechanical contributions - McBrayer, Josefine D.; Harrison, Katharine L.; Allcorn, Eric; Minteer, Shelley D. (Frontiers in Batteries and Electrochemistry, 2023)
Silicon anodes are a promising candidate to increase the energy density of lithium ion batteries for electric vehicles. However, recently, they have been identified as having poor calendar life that is insufficient for commercial needs in addition to the well-known issue of poor cycle life resulting from large volume expansion. Here, a specially designed protocol with variable rest periods between intermittent cycling is used to evaluate the impact of mechanical disruption of the silicon and solid electrolyte interphase from cycling on calendar aging measurements. Silicon was found to undergo more mechanical degradation during calendar aging with intermittent cycling than graphite. However, Si anode capacity fade was still dominated by time, especially for rest periods greater than or equal to 1 month between cycling. Post mortem dQ/dV half cell analysis indicated this was mainly due to lithium inventory loss and an increase in electrode resistance. Isothermal microcalorimetry further demonstrated that silicon passivation is more disrupted than graphite passivation with intermittent cycling and suggested that there may be a chemical build-up of a detrimental species in the electrolyte, leading to a large spike in heat after the silicon and SEI are disrupted with cycling.